Keywords: Perceptions of Physica Physical Education Teachers' Perceptions of the Implementation of the Independent Curriculum Module in Elementary Schools in Tana Tidung Regency: Persepsi Guru Pendidikan Jasmani tentang Implementasi Modul Kurikulum Mandiri di Sekolah Dasar di Kabupaten Tana Tidung - muhammad jufri; Mashuru Eko Winarno (S&Co Publishing, 2026)
The present research aimed to portray how elementary school physical education teachers in Tana Tidung Regency perceive the implementation of the Independent Curriculum teaching module. A descriptive–quantitative survey design was employed to obtain an overall picture of these perceptions. Sixteen physical education teachers participated as respondents. Data were gathered using a structured questionnaire, and the responses were processed using percentage-based analytical techniques. Findings revealed that out of the 16 participating teachers, seven individuals (44%) fell into the “Very Good” classification, achieving an average score of 89%. This outcome suggests that nearly half of the respondents demonstrated an exceptionally strong grasp and proficiency in applying the teaching module mandated by the Independent Curriculum. Meanwhile, the remaining nine teachers (56%) were categorized as “Good,” with an average percentage score of 74%, indicating that the majority of teachers had adequate understanding and ability in compiling and implementing the teaching module components according to the Independent Curriculum. These findings indicate that overall, physical education teachers in Tana Tidung Regency have